2021
DOI: 10.1101/2021.10.06.21264641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative transmissibility of SARS-CoV-2 variants Delta and Alpha in New England, USA

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Delta variant quickly rose to dominance in mid-2021, displacing other variants, including Alpha. Studies using data from the United Kingdom and India estimated that Delta was 40-80% more transmissible than Alpha, allowing Delta to become the globally dominant variant. However, it was unclear if the ostensible difference in relative transmissibility was due mostly to innate properties of Delta's infectiousness or differences in the study populatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 29 publications
8
47
0
Order By: Relevance
“…The Delta variant of concern of SARS-CoV-2 has spread globally causing large outbreaks and resurgences of COVID-19 cases [1][2][3] . The emergence of Delta in the UK occurred on the background of a heterogeneous landscape of immunity and relaxation of non-pharmaceutical interventions 4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…The Delta variant of concern of SARS-CoV-2 has spread globally causing large outbreaks and resurgences of COVID-19 cases [1][2][3] . The emergence of Delta in the UK occurred on the background of a heterogeneous landscape of immunity and relaxation of non-pharmaceutical interventions 4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…5L). These analyses demonstrate for the first time that the unique basal mutation G671S in the Delta VOC imposes a currently underappreciated level of evolutionary pressure driving the structural remodeling of its local environment, likely contributing to an elevated replication rate and to the increased viral load characteristic of Delta VOC (71)(72)(73)(74).…”
Section: Clusters 1-3 Collectively Contribute To Delta Voc Predatory Behaviormentioning
confidence: 91%
“…The copyright holder for this preprint this version posted January 7, 2022. ; https://doi.org/10.1101/2022.01.07.475295 doi: bioRxiv preprint possibility that the structural remodeling of the region around G671S contributes to the unique predatory behavior of the Delta VOC in driving the pandemic, likely through increased viral load (71)(72)(73)(74).…”
Section: Delta Voc Evolves a Novel Covariant Fitness Cluster 3 Driven By G671smentioning
confidence: 99%
“…Different studies tried to assess the increased infectiousness of the Delta variant. The authors of [8] found a 55 % increased reproduction number of Delta compared to Alpha, while [9] agreed on a range of 40-60 % and [7] even observed 58-120 % increased effective reproduction numbers. In our simulations, we will therefore consider Delta to be 40 − 60 % more infectious than the previously dominant Alpha variant, while 60 % is potentially closer to the true value.…”
Section: Alpha and Delta Variantmentioning
confidence: 98%
“…Additionally, we implement the effect of the B.1.617.2 (Delta) Coronavirus variant, which is considered to be 40% − 60% more infectious then the previously dominant B.1.1.7 (Alpha) variant; cf. [7][8][9]. In this paper, we focus on the comparison of different strategies based on our mathematical model that was already validated in [6].…”
Section: Introductionmentioning
confidence: 99%